MODERN INTERNATIONAL PRACTICES OF MOTIVATION DEVELOPMENT TO WORK IN ONLINE FORMAT AS A COMPONENT OF PROFESSIONAL TRAINING (Innovative professional education, 2024)
The question of improvement of the motivation of specialists in the field of special and inclusive education to work in online format according to European experiences and practiceshas been raised. The variability of professionally important qualities of specialists in thesocial field is related to the complexity and diversity of the functions they perform in the conditions of interaction with different contingents in constantly changing social and professional conditions of activity. The values of online education in the global and national dimensions havebeen delighted. An analytical review of research’s results has been conducted.
Keywords: motivation, online format, special course, management, specialist in the fied of social education